Competition Law and Financial Crime : a Comparative Analysis of International Responses to Market Manipulation - Johnson, Diana (Law teacher) (Routledge, 2025)
"Financial crime is a significant drain on economies across the world. This book looks at one aspect of financial crime, that of benchmark interest rate manipulation by competing banks, with the aim of identifying the best approach for the United Kingdom to take to the enforcement of laws against future benchmark manipulation. The manipulation of any benchmark interest rate by bankers, colluding for their own gain, is likely to negatively affect a large proportion of the population as many people have loans pegged to a benchmark interest rate. This monograph investigates the approach the UK took to enforcing action against the benchmark manipulation which took place in the London Interbank Offered Rate and the Foreign Exchange benchmark manipulation scandals. As part of this investigation, the approaches taken in the European Union and the United States of America are examined and compared to the approach taken in the UK to the same crime, to draw conclusions and make recommendations to improve the UK approach for future instances of benchmark manipulation. The work fills an important gap in the literature by comparing and evaluating the laws and enforcement policies pertaining to the use of competition law in counteracting benchmark manipulation in the UK, EU and US. It argues that competition law is an effective enforcement tool when used in the financial services sector and that it provides regulators with a wide range of enforcement options when a breach of competition law is established. The book will be a valuable resource for academics, researchers and policy-makers working in the areas of Financial Crime, Competition Law, Comparative Law and Criminal Justice"-- Provided by publisher.
Keywords: Commercial crimes -- Law and legislation.; Competition, Unfair.; elektronické knihy; electronic books